Grand Bocas, Trinidad, B.W.I - (:unkn) unknown (Waterman the Hatter, Clothier and Outfitter, 2009)
A picture of the Grand Bocas or Boca Grande with the view of two islets and rocks jutting out of the water. This marine channel can be found off the north west peninsula of Trinidad with the Caribbean Sea to the north of it and the Gulf of Paria to the south.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Ocean--Trinidad and Tobago; Islands--Trinidad and Tobago